1989
DOI: 10.3109/02688698909001023
|View full text |Cite
|
Sign up to set email alerts
|

Spinal Cord Compression Due to Thoracic Disc Herniation: Results of Microsurgical Posterolateral Costotransversectomy

Abstract: Fifteen consecutive patients with thoracic disc herniation treated by posterolateral microsurgical costotransversectomy are described. With appropriate modifications to the standard technique, costotransversectomy was found to be a suitable approach even for calcified central discs, and discs which had eroded intradurally. All patients had evidence of spinal cord compression preoperatively with varying degrees of leg weakness. The results of surgery are discussed. Ten patients who were disabled but ambulant sh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0
5

Year Published

1992
1992
2016
2016

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 19 publications
0
6
0
5
Order By: Relevance
“…Although they provided interesting comparisons, these lack validity because surgical and anesthetic procedures as well as postoperative management practices were vastly different for procedures performed in that era. 5,7,8,12,14,18,27,31,32,43,44,48,50,55 For example, in a thoracotomy or costotransversectomy procedure performed today for the treatment of an uncomplicated thoracic lesion, the incision would be smaller and the operating time, postoperative pain medications, and LOS would likely be cut by 50% compared with the same procedure a decade ago. Even today, LOS and operating time vary widely between surgeons and their respective institutions (Table 5).…”
Section: Neurological and Surgical Outcomementioning
confidence: 97%
See 1 more Smart Citation
“…Although they provided interesting comparisons, these lack validity because surgical and anesthetic procedures as well as postoperative management practices were vastly different for procedures performed in that era. 5,7,8,12,14,18,27,31,32,43,44,48,50,55 For example, in a thoracotomy or costotransversectomy procedure performed today for the treatment of an uncomplicated thoracic lesion, the incision would be smaller and the operating time, postoperative pain medications, and LOS would likely be cut by 50% compared with the same procedure a decade ago. Even today, LOS and operating time vary widely between surgeons and their respective institutions (Table 5).…”
Section: Neurological and Surgical Outcomementioning
confidence: 97%
“…[2][3][4][5]10,32,33,38,52,53 Previous literature on thoracic disc surgery was often collected in a retrospective fashion, spanning many years, and data on patients were often pooled, making it difficult to interpret the patient's initial clinical presentation and their neurological outcomes. 5,7,8,12,14,18,27,31,32,42,44,48,50,55 As a result, there is a lack of quantifiable surgical data as well as information on overall neurological outcome after surgical treatment for these difficult-to-reach lesions. The purpose of this investigation was to establish criteria for outcome measurement in thoracic disc surgery.…”
mentioning
confidence: 98%
“…[1] Young et al reported that back pain in 27% of patients and the other common symptom in this series was motor weakness. [3] Sensory disturbances, which had not been specified, were noted in 11% of patients. BSS presentation was Letters to Editor observed in 7% of patients.…”
Section: Thoracic Disc Herniation With Affection Of the Anterior Spinmentioning
confidence: 97%
“…Пåðåäíèå îòäåëы МПÄ èñïыòыâàюò бîëüшóю íàãðóзêó, ïîэòî-мó îíè â ïåðâóю îчåðåäü ïîðàaeàюòñя ïðè ãðóäíîм îñòåîхîíäðîзå. Â äàëüíåéшåм ïðè фîðмèðîâàíèè зàäíåé ïðîòðóзèè ñîзäàюòñя ïðåäïîñыëêè äëя íåñòàбèëüíîñòè â ïîзâîíîчíî-äâèãàòåëüíîм ñåãмåíòå, à ïîñëå îïåðàòèâíîãî âмåшàòåëüñòâà ñ óäàëåíèåм чàñòè êîñòíых ñòðóêòóð, îбъåм êîòîðых зàâèñèò îò âыбðàííîãî îïåðàòèâíîãî äîñòóïà, ðèñê âîзíèêíîâå-íèя íåñòàбèëüíîñòè óâåëèчèâàåòñя [5,8,12,16]. Эòî îбóñëîâëèâàåò íåîбхîäèмîñòü ñòàбèëèзàöèè ïîзâî-íîчíî-äâèãàòåëüíîãî ñåãмåíòà ïîñëå îïåðàòèâíîãî âмåшàòåëüñòâà íà ãðóäíîм îòäåëå ïîзâîíîчíèêà.…”
Section: иíñòèòóò íåéðîхèðóðãèè èì àêàä àï ðîìîäàíîâà àìí уêðàèíыunclassified